Effect of Trichoderma on the seed health tubers production of potato varieties under Rhizoctonia solani in greenhouse condition - Mohammad Entesari; Behnam Kamkar; Farshid Ghaderifar; Masoud Ahmadzadeh (علوم و فناوری بذر ایران)
To evalute the effect of Trichoderma fungus on potato productin in the presence of Rhizoctonia solani, a three replicated greenhouse experiment was conducted in a randomized complete block design. Treatments were three strains of Trichoderma (i.e. Trichoderma harzianum (TR), Trichoderma virens (Tr2), Trichoderma atroviride (Tr3)), Rhizoctoniasolani Ag3 fungus and Agria and Sante varieties of potato provided by the seed and plant certification and registration institute. Root and shoot dry weight, stolon dry weight and number, tubers number and fresh weight were measured. the results showed that Trichoderma tretmeant could have a significant effect on the traits in the presence of fungus (pathogen-infected condition). Also, the virulence was significant decreased as compared to the contorol. Tr1 - Agria variety combined treatment had mor significant effect on the measured traits than the other combined treatments, so that dry weight of shoot and stolons, fresh weight of tubers and the number of tubers was the highest in Tr1 tretmeant which was increased as compared to the control as 80, 52, 70 and 175 percentage, respectively. Also Tr1 Treatment increased Antioxidant enzyme activity and proline content, while decreased lipid peroxidation.